2017
DOI: 10.1089/jpm.2016.0330
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Interventions for Patients with Heart Failure: A Systematic Review and Meta-Analysis

Abstract: Objective: To systematically characterize interventions and effectiveness of palliative care for advanced heart failure (HF) patients. Background: Patients with advanced heart failure experience a high burden of distressing symptoms and diminished quality of life. Palliative care expertise with symptom management and healthcare decision-making benefits HF patients. Methods: A systematic PubMed search was conducted from inception to June 2016 for studies of palliative care interventions for HF patients. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(152 citation statements)
references
References 53 publications
1
146
0
5
Order By: Relevance
“…In cancer, PC has been shown to improve quality of life and, in some cases, prolong it 39–41. A recent systematic review of PC in HF cited improved quality of life and symptoms, with decreased hospitalisations and in-hospital deaths 42. Although there is not comparable literature in the population of patients with severe valve disease, 29% of the patients included in the EuroHeart study had concomitant valve disease 43…”
Section: High Surgical Risk Implies the Need For Advance Care And Valmentioning
confidence: 99%
“…In cancer, PC has been shown to improve quality of life and, in some cases, prolong it 39–41. A recent systematic review of PC in HF cited improved quality of life and symptoms, with decreased hospitalisations and in-hospital deaths 42. Although there is not comparable literature in the population of patients with severe valve disease, 29% of the patients included in the EuroHeart study had concomitant valve disease 43…”
Section: High Surgical Risk Implies the Need For Advance Care And Valmentioning
confidence: 99%
“…Although heart failure differs in many aspects from cancer, it is recognized that heart failure patients have key typical palliative care needs similar to those with incurable malignant disease . A recently published review also describes that palliative care interventions that are combined with heart failure management can improve patient outcomes and decrease costs and utilization of care …”
mentioning
confidence: 99%
“…We had to deal with three very distinct breaking points of variable length, and we were not able to gather sufficient data points in all periods for a solid ITS, especially for the period after the early communication. For example, of our total study population of 39,496 patients, in August 2008, 177 patients started clopidogrel and were already using a GP drug.…”
Section: Discussionmentioning
confidence: 99%
“…In 1987 the Consensus trial 36 was published, which for the first time incontrovertibly demonstrated that the -at that time-poor outcome of patients with heart failure can be markedly improved with medical therapy. The first European guideline on the treatment of heart failure was published in 1997 37 , followed by revised guidelines in 2001 38 , 2005 39 , 2008 40 , 2012 41 and 2016. 42 In Chapter 4 we analysed in real-world data to what extent the European Society of Cardiology guidelines influenced prescription behaviour at discharge after a first hospital admission for heart failure, between 2001 and 2015.…”
Section: Outline and Scope Of This Thesismentioning
confidence: 99%
See 1 more Smart Citation